Assist?ncia pr?-natal ?s gestantes maiores de 35 anos: com a palavra, as enfermeiras - Alves, Luana Lemos (2024)
Pregnancy in women over 35 years old is increasing worldwide and is considered late pregnancy. Prenatal care for women who have a late pregnancy must be carried out rigorously, aiming to offer qualified assistance during the perinatal period, given the complications that may occur. It is important to carry out an analysis from the position occupied by the professional who is at the ?edge?, who deals directly with the user, regarding what are the main challenges they have been facing in prenatal care. The present study aimed to understand the main challenges experienced by nurses with regard to prenatal care for pregnant women over 35 years old, within the scope of Primary Health Care. The study has a qualitative and descriptive approach using research field. The study took place in the city of Salvador, capital of the State of Bahia, with 17 nurses being interviewed from Public Health Units belonging to the S?o Caetano-Val?ria Health District. From the interviews carried out, the analysis and discussion of cases were categorized into 03 distinct categories: difficulties in conducting prenatal care for women over 35 years old, potentialities in conducting prenatal care for women over 35 years old and strategies for improving care for pregnant women over 35 years old. Regardless of the age group of the pregnant women, in general, the biggest concerns of the professional nurses interviewed are related to the pathologies and risk conditions associated with the patients. The main challenges in prenatal care for pregnant women in the city of Salvador are related to carrying out laboratory tests and ultrasound, both in terms of access and in relation to the time it takes to deliver the reports. The commitment of the professionals interviewed was highlighted in terms of aiming to offer adequate prenatal care to patients, highlighting that the job performed, despite having many setbacks, has been rewarding, mainly due to the characteristics that are inherent to PHC, related to ties with the community.